Genome‐wide analyses of Liberibacter species provides insights into evolution, phylogenetic relationships, and virulence factors. (28th February 2020) - Thapa, Shree P.; De Francesco, Agustina; Trinh, Jessica; Gurung, Fatta B.; Pang, Zhiqian; Vidalakis, Georgios; Wang, Nian; Ancona, Veronica; Ma, Wenbo; Coaker, Gitta
Abstract: ' Candidatus Liberibacter' species are insect‐transmitted, phloem‐limited α‐Proteobacteria in the order of Rhizobiales . The citrus industry is facing significant challenges due to huanglongbing, associated with infection from ' Candidatus Liberibacter asiaticus' (Las). In order to gain greater insight into ' Ca. Liberibacter' biology and genetic diversity, we have performed genome sequencing and comparative analyses of diverse ' Ca . Liberibacter' species, including those that can infect citrus. Our phylogenetic analysis differentiates ' Ca. Liberibacter' species and Rhizobiales in separate clades and suggests stepwise evolution from a common ancestor splitting first into nonpathogenic Liberibacter crescens followed by diversification of pathogenic ' Ca. Liberibacter' species. Further analysis of Las genomes from different geographical locations revealed diversity among isolates from the United States. Our phylogenetic study also indicates multiple Las introduction events in California and spread of the pathogen from Florida to Texas. Texan Las isolates were closely related, while Florida and Asian isolates exhibited the most genetic variation. We have identified conserved Sec translocon (SEC)‐dependent effectors likely involved in bacterial survival and virulence of Las and analysed their expression in their plant host (citrus) and insect vector ( Diaphorina citri ). Individual SEC‐dependent effectors exhibited differential expression patterns between host and vector, indicating that Las uses its effector repertoire to differentially modulate diverse organisms. Collectively, this work provides insights into the evolution of ' Ca. Liberibacter' species, the introduction of Las in the United States and identifies promising Las targets for disease management. Abstract : Comparative analyses of genomes provide insights into the evolution of ' Ca. Liberibacter' species and the introduction of huanglongbing in the United States, and identifies promising conserved Sec translocon‐dependent effector targets for disease management.